Developing Situation of Tea Harvesting Machines in Taiwan - Wu, C. C. (Engineering, Technology & Applied Science Research, 2015)
In recent years rapid social change and industrial and commercial development in Taiwan has lead to migration of rural labor, population ageing, high wages and labor shortages, which resulted in significant problems for the tea industry. Thus, mechanization in the tea industry emerges as the direction for the future. According to a survey, tea harvesting and tea manufacturing use 87% and 5% of available labor, so the mechanization of tea harvesting is a priority. The application and development of tea harvesting machines worldwide and especially in Taiwan in recent years is investigated in this paper. Recommendations are made for the implementation of tea harvesting machinery in Taiwan in the future. This report may also used as a reference for the use of mechanical harvesting.